THE KEY ROLE OF PIN PROTEINS IN AUXIN TRANSPORT IN ARABIDOPSIS THALIANA ROOTS - V. V. Kovrizshnykh; N. A. Omelyanchuk; T. Pasternak; V. V. Mironova (Вавиловский журнал генетики и селекции, 2015)
The phytohormone auxin is the key factor in plant morphogenesis. Being unevenly distributed in plant tissues, it forms gradients and concentration maxim а, according to which cells grow, divide, and differentiate. The family of PIN-FORMED (PIN) proteins, transmembrane transporters of auxin, play the key role in the formation of auxin gradients. The plant root is the most appropriate model for studying the regulation of morphogenesis, because of its relatively simple cellular organization. This review concerns the expression patterns of PIN transporters and their contribution to auxin distribution in the root of Arabidopsis. Mathematical models that prove the relationship between the expression pattern of PIN proteins and auxin distribution in the root meristem are discussed.